Unpredictable risk enhances induced neophobia in northern red-bellied dace. (October 2020) - Brown, Grant E.; Demers, Ebony E.M.; Goldman, Jack A.; Singh, Annick; Chivers, Douglas P.; Ferrari, Maud C.O.
Abstract : Neophobia, the fear response of organisms towards novel cues, is a phenotypically plastic trait that manifests among prey that experience uncertain, often high levels of risk. Prey that find themselves in uncertain or highly variable risk environments over ecological and evolutionary time could benefit from reducing the costs associated with 'making a bad decision' when they detect novel or unknown predatory threat. Hence, understanding ecological uncertainty in the context of prey decision making is of key interest. While ecological uncertainty remains a poorly defined concept, the degree of uncertainty experienced by prey, and by extension neophobia, should be influenced by the predictability of risk. Here, we test whether prey exposed to the same overall level of predation risk exhibit stronger neophobic responses towards a standardized novel cue when they experience the risk in an unpredictable versus predicable manner. Northern red-bellied dace, Chrosomus eos, exposed to conspecific alarm cues (risk cue) over a 3-day period exhibited a stronger intensity of neophobia than those exposed to low-level risk. However, if the alarm cues were presented as three exposures ranging in volume, the dace exhibited stronger neophobic responses compared to dace exposed to three equal exposures per day. Similarly, our second experiment showed that dace exposed over 3 days to elevated risk at random versus consistent times each day had stronger neophobic response under the random schedule. Combined, our results demonstrate that the degree of predictability of risk is a critical factor determining uncertainty and neophobia exhibited by prey populations. Highlights: Neophobia is a phenotypically plastic response by prey to uncertain risk. Elevated mean predation risk and predictability of risk should drive neophobia. We exposed dace to predictable or unpredictable risk at high vs low levels. Neophobic responses were stronger following exposure to unpredictable risk. Risk unpredictability is a critical factor driving neophobia within prey populations.